Review on Insurance and their Present Status in Nepalese Economy - Khanal, Nirdosh (Management Dynamics, 2020)
The study aims to overview the types of insurance operating in Nepal, product delivered by them and status of insurance market in Nepalese economic development. The paper is based on secondary data and literature reviews. Insurance can be acknowledged as tool that shares risk, offers financial protection, minimizes the financial distress and accelerates the pace of economic growth. Insurance encourages saving in the society and collects the scattered fund in term of premium and invest for maximization. Presently 40 insurance companies (19 life insurance, 20 non-life insurance and 1 reinsurance) are operating in Nepal providing diversified range of services. Recently agriculture insurance on crop and livestock sector and health insurance policy is being offered through many governmental and private insurance companies of Nepal. Insurance Board statistics of 2017 revealed total premium of 46.97 billion rupees and 2.03% contribution in total gross domestic product. We cannot deny the fact that insurance market of Nepal is witnessing major obstacles in terms of new product innovation, service issues related to consumers and time lapse of long-term policy. The study concludes that with little improvisation based on market research and consumer awareness can lead insurance companies & the concept to a peak level in Nepal.